2018
DOI: 10.1038/s41598-018-27955-4
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion characteristics of radioactive materials estimated by wind patterns

Abstract: The radioactive materials are generally concentrated downwind of their origins when the prevailing winds blow continuously in one direction. If this principle determined the pattern of dispersion in all cases, dispersion directions could be estimated by wind patterns. However, this hypothesis has not been sufficiently verified because of the complexity of dispersion processes and weather systems. Here, we show that dispersion directions, which are divided into four ranges, can be estimated by wind patterns usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In this study, we simulated a leak of a radioactive nuclide for 8 h from El Dabaa reactor every day for 5 days in the future using the FLEXPART dispersion model. The results of the simulations were in agreement with those obtained in previous studies of the Chernobyl case, reporting that the radioactive material moved corresponding to the prevailing wind in the lower troposphere even though the maximum of emission height was more than 2000 m from the surface [7]. The risk estimates exhibit seasonal variability, with increased surface level concentration and deposition of 137Cs during summer where the pattern extended towards the south and east.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we simulated a leak of a radioactive nuclide for 8 h from El Dabaa reactor every day for 5 days in the future using the FLEXPART dispersion model. The results of the simulations were in agreement with those obtained in previous studies of the Chernobyl case, reporting that the radioactive material moved corresponding to the prevailing wind in the lower troposphere even though the maximum of emission height was more than 2000 m from the surface [7]. The risk estimates exhibit seasonal variability, with increased surface level concentration and deposition of 137Cs during summer where the pattern extended towards the south and east.…”
Section: Discussionsupporting
confidence: 88%
“… 93 Recently, there are several ML applications to forecast the radioactive plume direction—up to several hours in advance—by analyzing wind patterns. 94 …”
Section: Discussionmentioning
confidence: 99%
“…For example, when the prevailing winds blow continuously in one direction, generally the radioactive materials are concentrated downwind from the source. By using a machine learning approach to characterize radionuclide dispersion from the Fukushima Daiichi accident release, Yoshikane and Yoshimura [15] pinpointed that radioactive plume directions and extensions can be estimated effectively by wind patterns. In a second study, Yoshikane et al [16] showed that nocturnal local wind patterns around the Fukushima site had played a notable role in the long-distance transport of radioactive plumes.…”
Section: Introductionmentioning
confidence: 99%